Prevalence of Aflatoxin B1 in rice bran and some associated factors - INDIRA KALYANASUNDARAM, T. VINCENT PAUL ELANGOVAN and (Indian Phytopathology, 2002)
A wide survey on the prevalence of aflatoxin B1 (AFB1) in rice bran was conducted using 142 samples collected from 55 rice mills in coastal and interior districts of Tamil Nadu, Andhra Pradesh and Karnataka, India. A total of 62% of the samples contained AFB1, and the levels far exceeded the permissible limit of 50 ppb, with 60% of the positive samples having 50-500 ppb and 30% up to 2000 ppb. The mycoflora of bran included >20 osmophilic species, of which Aspergillus flavus showed the highest frequency (75%) as well as abundance (37.6%). The high frequency and high levels of AFB1 was correlated with sanitation in the rice mills which were suspected to be a major source of contamination of bran with aflatoxigenic fungi/aflatoxin.